TEMPO DEBITO. Sulla temporalità all’epoca del corona virus (Materiali di Estetica. Terza serie, 2020)
Starting from the expression “in due course of time” or “in due time” the present contribution develops a series of reflections on the way each subject inhabits time in the era of Covid-19. In order to disrupt narcissistic withdrawal as well as the idea of traumatic loss of freedom due to our severe restricted mobility the author highlights the unconscious overdetermination of the pandemic crisis. The feeling of stuckness caused by lockdown compels Western societies to reconsider neoliberalism’s temporal regimes of growth, decline and acceleration. In the wake of Freud and Lacan the author argues that each subject is inscribed in Nachträglichkeit. The assumption of responsibility is subordinate to this retroactive dimension of time which determines emotional life, desires, acting out as well as new ideas and forms of cultural production in relation to others and Otherness. Drawing on poetry and literature as well as on Legendre’s studies the contribution assumes filiation as descent or derivation which inscribes the subject in a chain of debt investing the whole of human life on earth. Filiation entails being in the world in such a way that in due course of time, after an appropriate interval desires are fulfilled and the responsibilities towards those who have generated us are situated in the transgenerational order. This working through of individual conflicts impinges on social and moral responsibilities so that a new ontology of world politics becomes possible.
Keywords: Era of Covid-19; Nachträglichkeit vs Presentism; Lockdown vs Creativity; Filiation; As-Yet Situation; Psychic Change; Transgenerational Legacy